A comparative study on leaf anatomy and photosynthetic characteristics of different growth stages of Horsfieldia hainanensis - Xu, Jianwang; Tang, Jianmin; Jiang, Haolong; Zou, Rong; Wei, Xiao (PeerJ, 2024)
The rare and endangered wild plant, Horsfieldia hainanensis, has been listed as a second-level key protected plant in China. Currently, its habitat is severely damaged, and the population has dramatically declined, necessitating urgent intervention for protection. In this study, the aim was to explore the correlations and differences from the perspectives of photosynthetic characteristics and leaf structure, providing scientific references for in-situ conservation and ex-situ cultivation. The results revealed the following: (1) The maximum net photosynthetic rate (Pmax) and light saturation point (LSP) of mature trees were significantly higher than those of seedlings, while the light compensation point (LCP), CO2 compensation point (CCP), and CO2 saturation point (CSP) were significantly lower in seedlings. (2) The average daily net photosynthetic rate of mature trees was significantly higher than that of seedlings. When both mature trees and seedlings exhibited a “midday depression” phenomenon, accompanied by an increase in intercellular CO2 concentration (Ci), it indicated that the “midday depression” was caused by non-stomatal limiting factors. (4) Both mature trees and seedlings showed peak values of water use efficiency (WUE) under low light conditions. Mature trees had smaller upper and lower epidermis thickness but larger leaf thickness, and their leaf structure, characterized by well-developed palisade and spongy tissues, conformed to the cellular structure adaptations for low light. Therefore, both were more adapted to low light conditions. (5) The stomatal density (SD) and individual stomatal area (SA) of seedlings were significantly higher than those of mature trees. (6) The total chlorophyll content of mature trees was significantly higher than that of seedlings, while the chlorophyll a/chlorophyll b ratio was significantly lower in mature trees and remained below three in both cases. In summary, the photosynthetic capacity and light adaptability of mature trees are stronger than those of seedlings, but both mature trees and seedlings exhibit shade-tolerant characteristics. For in-situ conservation, it is possible to promote the growth and development of seedlings by appropriately employing artificial “windowing” or shading methods based on the actual growth environment of the seedlings. In the case of ex-situ cultivation, seedlings should be provided with appropriate shading initially, while ensuring sufficient moisture and CO2 concentration. As the plants grow, the shading intensity can be gradually reduced. Once the plants reach maturity, they have a broader range of light adaptability and can be transplanted to environments with less shading.
Keywords: Horsfieldia hainanensis; Photosynthetic characteristics; Leaf structure; Photosynthetic pigments; Photosynthetic response; Population conservation